Ad Novas-Cesenatico. From Roman Road to Late Antique Wooden Structures. An Interim Report on the Evaluation Test Pits and Excavation at Cà Bufalini, 2006 - Sami, Denis; Baldi, Elena; Booth, Anna; Chinni, Tania; Salamone, Filippo; Toniolo, Luana (Associazione Internazionale di Archeologia Classica, 2014)
This paper presents the preliminary data from excavations undertaken at Cà Bufalini in Cesenatico in April 2006. This was the pilot fieldwork from which developed the Ad Novas-Cesenatico Project 2008-13 organised by Denis Sami and Neil Christie from the University of Leicester. During the 2006 season four test trenches were opened. This paper outlines the evidence retrieved both of late antique (fifth - sixth century AD) wooden structures as well as of a substantial paved Roman road. Potentially, the Cà Bufalini site may relate to the likely statio of Ad Novas depicted on the Tabula Peutingeriana.